(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
The Nueva corónica y buen gobierno is often seen as a letter to the king, but it should be remembered that Felipe Guaman Poma de Ayala also dreamed of a wide distribution of his book, which is why he strove to give his manuscript the appearance of a printed book, as if it were a clean copy addressed to an editor. In this article, dedicated specifically to the front page of Guaman Poma’s chronicle, I compare this page with contemporary Spanish equivalents to discuss the high level of imitation the author yearned for and the final result.